Toosendanin targeting eEF2 impedes Topoisomerase I & II protein translation to suppress esophageal squamous cell carcinoma growth - Xuechao Jia; Penglei Wang; Chuntian Huang; Dengyun Zhao; Qiong wu; Bingbing Lu; Wenna Nie; Limeng Huang; Xueli Tian; Pan li; Kyle Vaughn Laster; Yanan Jiang; et al. (Journal of Experimental & Clinical Cancer Research, 2023)
Abstract Background Although molecular targets such as HER2, TP53 and PIK3CA have been widely studied in esophageal cancer, few of them were successfully applied for clinical treatment. Therefore, it is urgent to discover novel actionable targets and inhibitors. Eukaryotic translational elongation factor 2 (eEF2) is reported to be highly expressed in various cancers. However, its contribution to the maintenance and progression of cancer has not been fully clarified. Methods In the present study, we utilized tissue array to evaluate eEF2 protein expression and clinical significance in esophageal squamous cell carcinoma (ESCC). Next, we performed knockdown, overexpression, RNA-binding protein immunoprecipitation (RIP) sequence, and nascent protein synthesis assays to explore the molecular function of eEF2. Furthermore, we utilized compound screening, Surface Plasmon Resonance (SPR), Isothermal Titration Calorimetry (ITC) assay, cell proliferation and Patient derived xenograft (PDX) mouse model assays to discover an eEF2 inhibitor and assess its effects on ESCC growth. Results We found that eEF2 were highly expressed in ESCC and negatively associated with the prognosis of ESCC patients. Knocking down of eEF2 suppressed the cell proliferation and colony formation of ESCC. eEF2 bond with the mRNA of Topoisomerase II (TOP1) and Topoisomerase II (TOP2) and enhanced the protein biosynthesis of TOP1 and TOP2. We also identified Toosendanin was a novel inhibitor of eEF2 and Toosendanin inhibited the growth of ESCC in vitro and in vivo. Conclusions Our findings show that Toosendanin treatment suppresses ESCC growth through targeting eEF2 and regulating downstream TOP1 and TOP2 biosynthesis. eEF2 could be supplied as a potential therapeutic target in the further clinical studies.